Across the Great Divide: Archival Discourse and the (Re)presentations of the Past in Late-Modern Society - Dodge, Bernadine (Archivaria, 2002)
This article examines the implications for archival discourse in a late-modern world of technoculture featuring the digital re-mediation of documents, texts and images. Issues such as provenance, authority, memory and evidence are affected in a variety of ways once documents and photographs are detached from their original settings and enter cyberspace. Many theorists of the postmodern decry the effects of speed and time distortions associated with the age of the machine. Many also regret the passing of the autonomous, grounded individual characterized by an inherently stable self. This article suggests that there may be advantages to loosening some of the ties that bind us to traditional ways of looking at archival practices in late-modern society.